Toward Sustainable 6G Cellular System Core-Network-Level Traffic Aggregation: An Empirical Study - Takeo Ogawara; Sohei Itahara; Akito Suzuki; Masaki Suzuki (IEEE Access)
In this paper, the feasibility of core network (CN)-level traffic aggregation for multigeneration cellular radio access networks (RAN) is experimentally demonstrated. CN-level aggregation aims to integrate emerging radio access technologies into the legacy cellular network without modifying the legacy RAN by effort on CN, facilitating the smooth spread of emerging technologies. However, CN-level aggregation’s positioning remains unclear due to the lack of direct comparisons with RAN-level aggregation, which has been widely commercialized and inherently impacts the legacy infrastructure. To fill the knowledge gap, an extensive performance comparison between the RAN- and CN-level aggregations is provided. The experimental results reveal that CN-level aggregation achieves competitive throughput performances compared with RAN-level aggregation and does not impact the legacy RAN.